2021
DOI: 10.3390/nu13020438
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Interactions between the Menstrual Cycle, Exercise Training, and Macronutrient Intake in Women: A Review

Abstract: Women have a number of specificities that differentiate them from men. In particular, the role of sex steroid hormones and the menstrual cycle (MC) significantly impact women’s physiology. The literature has shown nonlinear relationships between MC, exercise, and nutritional intake. Notably, these relationships are bidirectional and less straightforward than one would suppose. For example, the theoretical implications of the MC’s phases on exercise performance do not always translate into relevant practical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 145 publications
0
10
0
3
Order By: Relevance
“…It is well accepted that intake in the magnitude of 1.2 to 2 g.kg.BW −1 is enough to meet physical requirements [ 20 ]. Although these values were determined for men, there is no reason to believe they should be different for female athletes [ 7 ]. In line with previous studies [ 13 , 40 , 43 , 47 , 48 ], we observed that the team’s protein intake met the recommendations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that intake in the magnitude of 1.2 to 2 g.kg.BW −1 is enough to meet physical requirements [ 20 ]. Although these values were determined for men, there is no reason to believe they should be different for female athletes [ 7 ]. In line with previous studies [ 13 , 40 , 43 , 47 , 48 ], we observed that the team’s protein intake met the recommendations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, most of this information has been reported for male football players [ 2 , 4 , 5 , 6 ], and little is known of female football players. The physiological (e.g., hormonal milieu) and morphological (e.g., body composition) gender differences become more evident when responding to various training/competition requirements [ 7 , 8 ]. For example, in match play, females covered less distance but at higher intensity levels (maximum speed greater than 15 km.h −1 ) than male players [ 9 ], even though most of the match time was spent on low-intensity activities, such as standing, walking and jogging [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies ha The promotion of PE in medicine and its influence on human health has led to the assimilation of the notion of "Exercise is Medicine" [202]. At the moment, a current research topic also looks at how estrogen/progestogen secretion is influenced by physical activity [203].…”
Section: Physical Exercise and Anti-inflammatory Effectsmentioning
confidence: 99%
“…Unhealthy nutrition attitudes and behaviors are quite common among women. The development of such behaviors involves a high risk for existing health conditions of slightly obese and obese individuals (Haghighat et al, 2021;Rocha-Rodrigues et al, 2021). The three most frequently studied areas of eating attitudes are uncontrolled eating, cognitive restriction, and emotional eating.…”
Section: Introductionmentioning
confidence: 99%